Ratib Tegak in Kerinci: Between Spirituality, Local Wisdom and Character Values in the Younger Generation - Jamin, Ahmad; Mirdad, Jamal (Fakultas Ushuluddin, Adab dan Dakwah IAIN Kerinci, 2022)
Ratib saman (Ratib tegak) is one of the local wisdoms of the Kerinci people which still exists today. Even though there are some criticisms of this ratib, the community still maintains and preserves this ratib and even makes it a ritual with a specific function and purpose. There are at least three things that are examined in this article, namely spirituality, local wisdom and character values ​​contained in the Ratib Tegak ceremony. This study uses a qualitative research design with a realist ethnographic approach. The research informants consisted of traditional leaders, clerics, ratib saman actors, and community leaders using a purposive sampling technique. Data was collected through interviews and documentation. Furthermore, the data were analyzed using analytical techniques from Miles and Huberman with three stages, namely data reduction, data display and drawing conclusions. The results of the research show that the Ratib tegak tradition contains elements of spirituality which the community believes is a form of obedience and obedience to the Almighty. It contains character values ​​that need to be applied to the younger generation which includes four aspects, namely thought, heart, exercise and taste.